Faktor-Faktor Yang Mempengaruhi Kepuasan Jamaah Umroh Dan Haji Dengan Persepsi Kesehatan Sebagai Variabel Moderating - Ardini, Lilis; Azizah, Muftiyatul; Munaa, Nihayatul (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Background – Indonesia is the country with the largest Muslim population in the world. This creates a lot of interest and demand for Hajj and Umrah in Indonesia. Hajj and Umrah are worship activities carried out by visiting Mecca and Medina and carried out in accordance with religious law. Since the city of Mecca reopened for Umrah pilgrims after Covid-19, thousands of people have visited various travel services that provide Umrah services. Various types of travel offers ranging from cheap prices, good aircraft facilities, and hotels close to the Kaaba. This offering strategy is carried out to get the attention of prospective Umrah pilgrims. Aim – In this study, the purpose of the study is to test whether service quality, price perception, trust, empathy and health perception influence customer satisfaction and whether health perception is able to moderate all these factors. Design / methodology / approach – This type of research is quantitative research, namely analyzing data in the form of numbers. The data used in this research is primary data which is data directly obtained from the first data source. Data was obtained from the results of a questionnaire distributed to respondents, namely Hikmah Travel pilgrims and Umrah pilgrims. The method used is multiple linear regression analysis with moderator effects. Findings – The results of this research are that the service quality variable (X1) has no effect on consumer satisfaction (Y), the price perception variable (X2) has no effect on consumer satisfaction (Y), the trust variable (X3) has no effect on consumer satisfaction (Y), the empathy variable (X4) has a significant effect on consumer satisfaction (Y), healthy perception (Z) moderates the influence of service quality (X1) on consumer satisfaction (Y), healthy perception (Z) is unable to moderate the influence of price (X2) on consumer satisfaction (Y), healthy perception (Z) is able to moderate the influence of trust (X3) on consumer satisfaction (Y), healthy perception (Z) is unable to moderate the influence of empathy (X4) on consumer satisfaction (Y). Conclusion - The ability of health perception to moderate consumer satisfaction is seen from the quality of service, price perception, trust is good, so this needs to be a concern for hajj and umrah services. However, the absence of health perception will actually result in compromised customer satisfaction. Research implication – Empathy has a significant effect on consumer satisfaction, so travel agencies should pay attention to the empathy factor so that it can increase consumer satisfaction and can be used to attract Hajj pilgrims to use their travel services. Apart from the empathy factor, healthy perceptions are able to moderate the factors of service quality and trust in customer satisfaction, so travel agencies must also pay attention to these factors to get potential customers. Limitations – The population in this research is Hajj and Umrah travel services in East Java, while the sample from this research is Umrah and Hajj pilgrims at Hikmah Travel.